2020
DOI: 10.1016/j.ebiom.2020.102861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma EGFR mutation as an early predictor of response of erlotinib plus bevacizumab treatment in the NEJ026 study

Abstract: Background: The NEJ026 Phase 3 study demonstrated that erlotinib and bevacizumab (BE)-treated NSCLC patients with EGFR mutations had significantly better progression-free survival (PFS) than those treated with erlotinib alone (E). This study included a prospective analysis of the relationship between the mutational status of EGFR in plasma circulating tumor DNA (ctDNA) and the efficacy of TKI monotherapy or combination therapy. We describe these results herein. Methods: Plasma samples were collected from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…One meta-analysis of 12 studies comparing EGFR-TKI monotherapy with chemotherapy concluded that patients with NSCLC and ex19del mutations had better progression-free survival (PFS; hazard ratio [HR]: 0.69; 95% CI: 0.57-0.82; p < 0.001) and overall survival (OS; HR: 0.61; 95% CI: 0.43-0.86; p = 0.005) than patients who had Leu858Arg mutations [9]. However, this analysis did not include the more recent Phase III trials: ARCHER 1050 (dacomitinib vs gefitinib), FLAURA (osimertinib vs gefitinib or erlotinib), NEJ026 (erlotinib plus bevacizumab) or RELAY (erlotinib plus ramucirumab) [10][11][12][13]. Other meta-analyses that compared monotherapy with erlotinib to combination therapy with erlotinib plus bevacizumab or ramucirumab concluded Table 1.…”
mentioning
confidence: 99%
“…One meta-analysis of 12 studies comparing EGFR-TKI monotherapy with chemotherapy concluded that patients with NSCLC and ex19del mutations had better progression-free survival (PFS; hazard ratio [HR]: 0.69; 95% CI: 0.57-0.82; p < 0.001) and overall survival (OS; HR: 0.61; 95% CI: 0.43-0.86; p = 0.005) than patients who had Leu858Arg mutations [9]. However, this analysis did not include the more recent Phase III trials: ARCHER 1050 (dacomitinib vs gefitinib), FLAURA (osimertinib vs gefitinib or erlotinib), NEJ026 (erlotinib plus bevacizumab) or RELAY (erlotinib plus ramucirumab) [10][11][12][13]. Other meta-analyses that compared monotherapy with erlotinib to combination therapy with erlotinib plus bevacizumab or ramucirumab concluded Table 1.…”
mentioning
confidence: 99%
“…In the NEJ026 study, results of the polymerase chain reaction clamp-based detection test in tissue/blood after drug resistance in the two groups showed that the proportion of T790M was 24% vs. 26%, respectively. The proportion of patients receiving follow-up osimertinib in the two groups was similar [ 13 , 25 ]. In the RELAY study after drug resistance, liquid biopsy samples were detected using a next-generation sequencing (NGS) method.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently published BELIEF trial, 16 activating EGFRm was detected in ctDNA in 55 of 91 (60%) patients with tumor EGFRm, and the patients with ctDNA EGFRm showed a correlation with a shorter PFS compared to ctDNA EGFRm‐negative patients. In a biomarker analysis of the NEJ026 phase III study comparing erlotinib plus bevacizumab combination therapy with erlotinib monotherapy in EGFR ‐mutated NSCLC, 17 patients without ctDNA EGFRm at baseline had longer PFS compared to patients with ctDNA EGFRm. In addition, patients who showed a negative conversion of ctDNA EGFRm from baseline to six weeks after the start of treatment had longer PFS compared with patients who had ctDNA EGFRm continuously detected after six weeks.…”
Section: Discussionmentioning
confidence: 99%